Gambaran Kualitas Hidup Pasien Kanker Serviks Yang Menjalani Radioerapi Di RSUD Arifin Achmad Provinsi Riau Periode 2011 – 2013 - Azizah "; Amru Sofian; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cervical cancer is a malignant tumor derived from primary squamous epithelial cells that grow on the surface of the epithelial or outer layer of the cervix, and is caused by virus infections Human Papiloma Virus (HPV). One of the given therapy on patients of cervical cancer is radiotherapy. Radiotherapy is done by people with cervical cancer that can affect the quality of life of the respondent which can be assessed by using the WHOQOL questionnair. The purpose of this research is to know the description of the quality of life of patients with cervical cancer undergoing radiotherapy. This research is descriptive research with cross sectional approach implemented in June 2014. There are 31 people with cervical cancer undergoing radiotherapy. From this research found the age of respondents in the age group 40-49 years 50-59 years and the age group 60-69 years were relatively the same lot. The majority of respondents were Malays (58,06 percent). Most respondents were the PRIMARY education (38,80). Most respondents work was as the IRT (90,32 per cent). The respondents underwent radiotherapy most within > 5 weeks (100%). On cervical cancer patients undergoing radiotherapy at the PROVINCIAL HOSPITAL Arifin Achmad Riau Province found the quality of life in both categories as much as 61,30%.Key word: cervical cancer, radiotherapy , quality of life